1968
DOI: 10.3382/ps.0470314
|View full text |Cite
|
Sign up to set email alerts
|

Sulfadimethoxine in Prevention of Turkey Coccidiosis

Abstract: group averages were 2.8 each. In comparison, the average 4-week feed conversion of the exposed control group was 3.2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
3

Year Published

1969
1969
2008
2008

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 3 publications
0
7
0
3
Order By: Relevance
“…This has been demonstrated experimentally for lasalocid and monensin, although the results are not always consistent (Mitrovic et al, 1979;Potter et al, 1986;Czarnecki, 1990). No significant reductions in weight gain were found in young poults given twice the approved use level of amprolium, diclazuril, maduramicin, robenidine or sulfadimethoxine (Mitrovic, 1968;Joyner & Norton, 1972;Vanparijs et al, 1989a;McDougald et al, 1990;Mathis, 1993). A slight weight gain depression was found, however, with 6 parts/10 6 halofuginone (McDougald, 1986).…”
Section: Chemotherapymentioning
confidence: 84%
See 2 more Smart Citations
“…This has been demonstrated experimentally for lasalocid and monensin, although the results are not always consistent (Mitrovic et al, 1979;Potter et al, 1986;Czarnecki, 1990). No significant reductions in weight gain were found in young poults given twice the approved use level of amprolium, diclazuril, maduramicin, robenidine or sulfadimethoxine (Mitrovic, 1968;Joyner & Norton, 1972;Vanparijs et al, 1989a;McDougald et al, 1990;Mathis, 1993). A slight weight gain depression was found, however, with 6 parts/10 6 halofuginone (McDougald, 1986).…”
Section: Chemotherapymentioning
confidence: 84%
“…Sulfaguanidine was reported to possess curative properties if administered in the feed for two or three successive days, but experimental details were not provided (Marsden & Martin, 1946). Many other sulfonamides were subsequently shown to have anticoccidial activity (Moore, 1949;Morehouse, 1949b;Peterson, 1949;Boyer & Brown, 1953;Mitrovic, 1968;Reid, 1972); of these, sulfaquinoxaline was to prove the most useful. Amprolium was also widely employed (Cuckler et al, 1961).…”
Section: Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfadimethoxine alone has been shown to be highly effective, therapeutically, against all pathogenic species of coccidia in chickens (0.05%) and turkeys (0.025%) when administered in the drinking water (Mitrovic and Bauernfeind, 1967) and efficacious in the prevention of turkey coccidiosis at 0.0125% in the feed (Mitrovic, 1968). Mitrovic (1967) reported that sulfadimethoxine was also effective in the therapy of fowl cholera in chickens (0.05%) and turkeys (0.025%) and infectious coryza in chickens (0.05%) when administered in the drinking water.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfadimethoxine alone has been reported to be highly effective, therapeutically, against all pathogenic species of coccidia in chickens (0.05%) and turkeys (0.025%) when administered in the drinking water (Mitrovic and Bauernfeind, 1967) and efficacious in the prevention of turkey coccidiosis at 0.0125% in the feed (Mitrovic, 1968). Mitrovic (1967) found that sulfadimethoxine was also effective in the therapy of fowl cholera in chickens (0.05%) and turkeys (0.025%) and infectious coryza in chickens (0.05%) when administered in the drinking water.…”
mentioning
confidence: 99%